Nutritional and Chemical-Physical Characterization of Fresh Pasta Gnocchi Prepared with Sea Water as New Active Ingredient - Gabriella Santagata (MDPI AG, 2021)
This study shows the chemical–physical and nutritional results obtained using food-grade sea water for the preparation of fresh pasta Gnocchi with respect to those prepared with tap water. Gnocchi obtained by mixing the flour with seawater (GSW) were compared with traditional Gnocchi made with tap water (GTW). The contents of sodium chloride, macro and micro elements, volatile molecules profile, thermal properties, and morphological analysis were investigated in both Gnocchi types. The analysis of chlorides showed that the samples prepared with sea water had a significantly lower NaCl content after cooking in comparison with those prepared with tap water. These results were also confirmed by the inductively coupled plasma (ICP) analysis for sodium content. The profiles of the volatile molecules acquired by gas chromatography-mass spectrometry (GC-MS) evidenced significant differences between the groups of aromatic molecules of the two typologies of samples. Morphological analysis evidenced that both raw and cooked GSW Gnocchi were structurally tightened whereas GTW Gnocchi showed a labile and weak macromolecular network. In addition, GSW Gnocchi was more thermally stable than GTW Gnocchi, as evidenced by thermogravimetric analysis (TGA).